Measures of Procedural Coercion in the Criminal Procedural Law of the Republic of Kazakhstan (Brief Analysis) - KENZHETAYEV, Chingiz D.; KORYAKIN, Ilya P.; KAN, Aleksandr G. (Journal of Advanced Research in Law and Economics, 2017)
The article considers issues related to the lack of conformity between the general logic of the criminal process and the actual norms of the Criminal Procedural Code of the Republic of Kazakhstan governing a coercive institution of the criminal process. The authors discuss complex issues on the purposes of measures of restriction and other measures of procedural coercion, and certain regulatory elements of this institution. They are described in detail as part of the study. This study applies the deductive method of research. The article analyzes a broad range of measures of criminal procedural coercion, including measures of restriction and other measures of procedural coercion, and ends with the authors’ conclusions on the problems connected with the application of the criminal procedural norms governing measures of coercion, the imperfection of certain criminal procedural norms under consideration, and the need to make some changes and amendments to the normative regulation of certain articles of the Criminal Procedural Code of the Republic of Kazakhstan constituting a part of measures of restriction and procedural coercion. A structure of measures of procedural coercion and their purposes has been established.